Human Neutrophils Present Mild Activation by Zika Virus But Reduce the Infection of Susceptible Cells - Aggio, Juliana Bernardi; Porto, Bárbara Nery; Duarte dos Santos, Claudia Nunes; Mosimann, Ana Luiza Pamplona; Wowk, Pryscilla Fanini (Frontiers in Immunology, 2022)
The emergence of the Zika virus (ZIKV) has highlighted the need for a deeper understanding of virus-host interactions in order to pave the way for the development of antiviral therapies. The present work aimed to address the response of neutrophils during ZIKV infection. Neutrophils are important effector cells in innate immunity implicated in the host’s response to neurotropic arboviruses. Our results indicate that human neutrophils were not permissive to Asian or African ZIKV strain replication. In fact, after stimulation with ZIKV, neutrophils were mild primed against the virus as evaluated through CD11b and CD62L modulation, secretion of inflammatory cytokines and granule content, production of reactive oxygen species, and neutrophil extracellular traps formation. Overall, neutrophils did not affect ZIKV infectivity. Moreover, in vitro ZIKV infection of primary innate immune cells did not trigger neutrophil migration. However, neutrophils co-cultured with ZIKV susceptible cell lineages resulted in lower cell infection frequencies, possibly due to cell-to-cell contact. In vivo, neutrophil depletion in immunocompetent mice did not affect ZIKV spreading to the draining lymph nodes. The data suggest that human neutrophils do not play an antiviral role against ZIKV per se, but these cells might participate in an infected environment shaping the ZIKV infection in other target cells.